2018
DOI: 10.1002/jum.14570
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Ultrasound Training in Obstetrics and Gynecology Residency Programs

Abstract: Recognizing the lack of clearly defined milestones in ultrasound training in OB-GYN residency, this study confirms the substantial heterogeneity in curricula between programs, highlighting a need for a standardized ultrasound curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Performing an obstetrical ultrasound (US) is an Accreditation Council for Graduate Medical Education milestone 1 and a Council on Resident Education in Obstetrics and Gynecology (CREOG) objective, 2 but many residency programs lack US rotations. 3,4 Given the limited literature on resident-reported confidence in their US skills, this study aimed to assess resident comfort with obstetrical US and factors associated with performing US independently.…”
Section: Objectivementioning
confidence: 99%
“…Performing an obstetrical ultrasound (US) is an Accreditation Council for Graduate Medical Education milestone 1 and a Council on Resident Education in Obstetrics and Gynecology (CREOG) objective, 2 but many residency programs lack US rotations. 3,4 Given the limited literature on resident-reported confidence in their US skills, this study aimed to assess resident comfort with obstetrical US and factors associated with performing US independently.…”
Section: Objectivementioning
confidence: 99%
“…However, formal incorporation of advanced ultrasound trainingincluding Doppler studies and fetal anatomic surveys -is not included in the Accreditation Council for Graduate Medical Education (ACGME) directive of any medical training program other than fellowship training in MFM (Table 1). [4][5][6][7][8][9][10][11][12][13] Prior studies have demonstrated improved diagnosis of fetal anomalies when ultrasounds are interpreted by MFM physicians compared to other providers. 14,15 However, MFM providers are known to be concentrated in certain parts of the country, and there are many areas where traditional obstetric ultrasound care by an MFM physician is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of standardized training for ultrasound in obstetrics and gynecology [1]. Recent surveys of trainees across the USA and Europe report widespread variability in availability, quality, and methods of training and assessment, both within and across countries [2]. As ultrasound equipment has become more affordable, its use (particularly in low and middle income countries) has also increased.…”
Section: Introductionmentioning
confidence: 99%